Dialogue in family life - Brînzea, Nicolae; Silivestru, George-Ștefan (Technium Social Sciences Journal, 2022)
Dialogue is the main way of interpersonal communication and is based on the human ability to use its own organic systems that belong to the body to create and support it. Dialogue best facilitates the penetration into the soul of the other person. In the nucleus of the family, the dialogue provides a good part of the communication needs, but we must be aware of its power and its beneficial effects. Dialogue is essential to experiencing, expressing, and fostering love in marriage and family life. In the Christian family, prayer is a dialogue with a very powerful charge. Dialogue must be imbued with the spiritual essence of the Christian life. If we strive to live an orthodox life, the dialogue will not use substance that conflicts with the spiritual state. Through dialogue, love will be shared, one will try not to hurt one's neighbor, the other will be accepted as he is, etc.